Pemberdayaan Masyarakat dengan Pemanfaatan Sumber Energi Terbarukan pada Tambak Udang - . Jalaluddin; Abdul Rasyid Jalil; Rustan Tarakka; . Wardi (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2015)
Shrimp is very promising commodity of the Indonesian export commodities. One of shrimp cultivation fields is pond which is a place of aquaculture located near the beach. Application of renewable energy sources such as photovoltaic cell technology has been prepared to provide energy supply integratedly in the shrimp ponds in Pinrang District of South Sulawesi. Energy needed in the shrimp ponds is to provide energy supply for some supporting equipments such as aerator water mill, lighting, water pump, and others. Community empowerment activity was carried out in order to empower communities in Pinrang District of South Sulawesi in application of renewable energy resources in their shrimp ponds. This activity was arranged in self supporting energy concept in the shrimp pond and supported by a program of Kuliah Kerja Nyata–Program Pemberdayaan Masyarakat (KKN-PPM) DIKTI. Equipment manufacture of photovoltaic cell prototype as energy sources of aerator waterwheel and lighting in the shrimp pond has been completed. Some community groups of shrimp farmers have been trained in the manufacture and operation of the photovoltaic cell equipment.